Engineering geology investigation and numerical modelling design of the Ramp 12 highwall - Roache, B; Johnstone, AR (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
The Goonyella Riverside Mine is located in the Bowen Basin of Queensland, Australia, and has been in constant operation since 1971. Seams of metallurgical coal are mined from a series of ramps (pits) using strip mining techniques and highwalls are formed by dragline excavation. A 750 m long, 100 m high, progressive highwall failure was monitored and safely managed at Ramp 12 during 2016. Engineering geology investigations commenced at this time to determine the mechanism of slope movement. The slope failure was attributed to a number of structural influences, most interesting of these being the overbank bedding structures combining with jointing in the interburden Permian sedimentary rock. A number of questions needed to be answered by site management, including how to stabilise and remove a large and actively moving highwall in a responsible and safe manner and to correctly account for the identified failure mechanism in design of the next highwall strip position. A three dimensional numerical approach that could account for the failure mechanism was selected and was used to back analyse the progressive development of the failure. The numerical model was then used to look forward and design the position and size of a stabilisation buttress and the highwall slope configuration for the advancing highwall. A full case study is presented, from identification and management of the slope instability, to developing an understanding of the failure mechanism, slope remediation, numerical modelling design and ongoing highwall performance of the redesigned pit highwall.
Keywords: case study; slope failure; numerical modelling